Estandarización de una PCR y qPCR para detectar y cuantificar Fowl Adenovirus Tipo 4 (FAdV-4) en FARVET S.A.C, 2017-2018 - Chávez Montenegro, Víctor Elías (2019)
The diseases produced by avian adenovirus Type 4 (FAdV-4) are transmitted vertically and horizontally causing great economic losses in the poultry sector, that is why there is the need to carry out a process of standardisation of a Polymerase chain in reaction (PCR) to detect and quantify our virus of interest. To this end, in the present investigation, it was carried out in three (03) phases: The first consisted in the preparation of the internal reference material where the DNA was extracted, from a culture of EB66 cells, measuring its quantity of the Amplicon through the Fluorometer Qubit 2.0. The second phase was to standardize conventional PCR, in this phase we proceeded to the selection of the specific primers (Primer´s), these were HHS *-2, HHS *-3 and HHS *-4; The test of its temperature gradient was carried out based on the Q5 PCR Kit® High-Fidelity 2X Master, followed by the test of concentration of primers, the test of sensitivity being 100, 3% for the three sets of primers and the test of specificity resulting in 46.15%, 100% and 91.67% respectively. The third phase consisted of standardizing PCR in real time, in this phase the sets of primers HHS *-3 (0.25 umol/L) were used with 107 viral copies, successive dilutions were performed with different concentrations of viral copies from the standard HHS7 to HHS0, making Use of the LightCycler Equipment® 480 SYBER Green I Master and the Rotor Gene 6000 Real-Time PCR, which gave us an accuracy and correlation coefficient of Pearson (R2) greater than 99%, detecting up to a concentration of amplicon ≥ 1pg/ul.